Prenominal Participial Phrases in Marathi, the Noun Phrase Accessibility Hierarchy, and Picture Nouns - Hook, Peter Edwin; Pardeshi, Prashant (Lingua Posnaniensis, 2013)
An introduction to Keenan and Comrie’s NPAH (noun phrase accessibility hierarchy) is followed by data showing to what extent Marathi’s PPP s (prenominal participial phrases) do and do not conform to it. The range of constructional variety inside a PPP is shown to be related to the tightness or looseness of the relation of the predicate inside the PPP to the nulled element. Examples are presented of the puzzling absence of Agent and Experiencer noun phrases inside PPP s. The paper ends with examples and discussion of the mismatch or transfer of PPP modifiers away from the NP denoting the ‘imagee’ or entity depicted in an image to the NP denoting the image itself.